Penyuluhan Dan Bimbingan Teknis Pencatatan Administrasi Keuangan Sederhana Pada Pengrajin Tenun Songket Tradisional Dusun Tangkep Lombok Tengah - Basuki Srihermanto; Suryaningsih; Dhea Candra Dewi; Ramdani Abd. Hafizh (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The purpose of this community service is to provide motivation, counseling and technical guidance on simple financial administration recording for traditional songket weavers in Tangkep Hamlet, Central Lombok using the concept of counseling. While the guidance techniques used are using question and answer techniques, counseling and development of science and technology. The results of the community service show that all participants showed a positive impression of the counseling and technical guidance on simple financial administration recording, and really hope for the continuation of this guidance. Although still simple, this guidance provides enlightenment for traditional weavers in Tangkep Hamlet. From this community service, it is hoped that it can provide added value for traditional songket weavers in Tangkep Hamlet, Central Lombok in particular and for the advancement of the business world in Indonesia in general.